TurboID‐mediated proximity labeling for screening interacting proteins of FIP37 in Arabidopsis - Xiaofang Li; Yanping Wei; Qili Fei; Guilin Fu; Yu Gan; Chuanlin Shi (Plant Direct, 2023)
Abstract Proximity labeling was recently developed to detect protein–protein interactions and members of subcellular multiprotein structures in living cells. Proximity labeling is conducted by fusing an engineered enzyme with catalytic activity, such as biotin ligase, to a protein of interest (bait protein) to biotinylate adjacent proteins. The biotinylated protein can be purified by streptavidin beads, and identified by mass spectrometry (MS). TurboID is an engineered biotin ligase with high catalytic efficiency, which is used for proximity labeling. Although TurboID‐based proximity labeling technology has been successfully established in mammals, its application in plant systems is limited. Here, we report the usage of TurboID for proximity labeling of FIP37, a core member of m6A methyltransferase complex, to identify FIP37 interacting proteins in Arabidopsis thaliana. By analyzing the MS data, we found 214 proteins biotinylated by GFP‐TurboID‐FIP37 fusion, including five components of m6A methyltransferase complex that have been previously confirmed. Therefore, the identified proteins may include potential proteins directly involved in the m6A pathway or functionally related to m6A‐coupled mRNA processing due to spatial proximity. Moreover, we demonstrated the feasibility of proximity labeling technology in plant epitranscriptomics study, thereby expanding the application of this technology to more subjects of plant research.